Women in Canadian Science and Technology before World War I: their Publication Record - Chu, Clara; MacDonald, Bertrum (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1988)
ABSTRACTLittle has been written about the work of women in Canadian science and technology, particularly for the period prior to the First World War. In this study, drawing largely on data in Science and Technology in Canadian History: A Bibliography of Primary Sources to 1914, we present a picture of the activity of almost 150 women authors. Representing 1.4% of all known authors of the period, these women wrote on a variety of scientific and technological topics and sometimes with a particular woman's viewpoint. The analysis highlights a number of changes which occurred throughout the nineteenth and early twentieth century.